Editorial: Freshwater science in the tropical anthropocene - Keke, Unique N.; Dalu, Tatenda; López-López, Eugenia; Arimoro, Francis O. (Frontiers in Environmental Science, 2023)
Freshwater ecosystems comprise only 0.01 % of the volume of water on Earth and 0.8 % of its surface while harboring approximately 10 % of the global diversity. They provide many ecosystem services, and harbor most species. The research topic “Freshwater Science in the Tropical Anthropocene” aimed to provide a critical overview of the current state of the gaps in our understanding of Freshwater Science in the Tropical Anthropocene. In our topic issue, a proposal for a Theory of Change to reverse the current Mexican freshwater fish extinction crisis is presented by Contreras-McBeath et al. Keke et al. described the importance of analyzing β- and γ-diversity to identify priority sites for conservation in Afrotropical lotic ecosystems. Biomonitoring is a key tool that provides a cost-effective and reliable way of assessing these changes in freshwater systems. In tropical freshwater ecosystems, freshwater ecosystems and aquatic biodiversity are often poorly understood. In this topic, a characterization of an Andean river using physicochemical water parameters and biotic quality indices (including aquatic macroinvertebrates) is presented by Álvarez-Tolentino et al. showing aquatic macroinvertebrates are suitable monitoring parameters for assessing water quality. Biomonitoring is a reliable, effective, and affordable assessment tool. The effect of introduced fish and seasonality on aquatic ecosystem conditions was assessed by Bellingan et al. using aquatic macroinvertebrates in the Keiskamma River system, South Africa. The DNA barcode (COI gene) was used for monitoring freshwater biodiversity and detecting changes in communities following perturbations to aquatic ecosystems in Mexico by Elías-Gutiérrez and Valdes-Moreno. Environmental DNA (eDNA) is a proving to be a promising tool for assessing freshwater biodiversity and environmental change in the Neotropics, although eDNA studies should be supported by a DNA baseline. Microplastics have emerged as a considerable global issue. Moyo presents a meta-analysis of microplastics assessing their impacts on the functional traits of tropical freshwater fish and invertebrates. Lopez et al. highlighted the limitations around studying the chemical nature of microplastic pollution of tropical freshwater systems, and as a first step assessed the occurrence, concentration, and distribution of suspected suspended microplastics in Ecuador.